Pelaksanaan Manajemen Pendidikan Inklusif di SDN 002 Pulau Palas Kecamatan Tembilahan Hulu Kabupaten Indragiri Hilir - Ahmad, Ahmad; Susrianto, Edi; Baidi, Nur; Khairuddin, Khairuddin; Muthalib, A. (Mitra PGMI: Jurnal Kependidikan MI, 2023)
The purpose of this study was to find out how the implementation of inclusive education management at SDN 002 Pulau Palas, Tembilahan Hulu District, Indragiri Hilir Regency and to find out what are the obstacles and supports in implementing inclusive education management at SDN 002 Pulau Palas, Tembilahan Hulu District, Indragiri Hilir Regency. Based on the results of the analysis of research data, the following conclusions are obtained: First: Implementation of Inclusive Education Management at SDN 002 Pulau Palas, Tembilahan Hulu District, Indragiri Hilir Regency has done quite well what the school principal has done because there are some of the results of observations and interviews that are in accordance with the results which are expected. In this case the school principal carries out several processes of implementing inclusive education in elementary schools, it is necessary to have an individual learning program. The program is useful for giving direction to learning by knowing the strengths, weaknesses, and interests of students, so an individualized program is directed at goals on the basis of needs and in accordance with the current level of ability. In addition, this program is also a vehicle for increasing business to provide more effective educational services. There are also learning programs using media so that students understand more. Second, the supporting factors in the Implementation of Inclusive Education Management at SDN 002 Pulau Palas, Tembilahan Hulu District, Indragiri Hilir Regency, namely that the school has a special accompanying teacher, each child has one special accompanying teacher. So this special accompanying teacher makes individual learning programs based on the results of the assessment. There is support from the local community, there are adequate facilities that support learning. Then the obstacle factor is not having professional staff such as doctors and psychologists.